Report of the Nomenclature Committee for Algae: 15 - Prud'homme van Reine, Willem F. (Taxon, 2017)
Three names are recommended for conservation against the names indicated: Gelidium bipectinatum (Rhodophyceae) against Fucus serra; Scrippsiella (Dinophyceae) against Heteraulacus and Goniodoma; and Gloeobacter violaceus (Cyanophyceae) against Aphanothece caldariorum, Gloeothece coerulea, and Gloeothece linearis, while two names are recommended for conservation with a conserved type: Chara hispida (Characeae) and Gloeothece (Cyanophyceae). Three names are recommended for outright rejection, Jania verrucosa (Rhodophyceae), Cyanospira (Cyanophyceae) and Goniodomataceae (Dinophyceae), but the name Gonyaulax catenella (Dinophyceae) should not be rejected. The Committee concluded that the names Geisleria Nitschke (Fungi) and Geissleria Lange-Bert. & Metzeltin (Bacillariophyceae) are not sufficiently alike to be confused.